Assessment of antioxidant and Hepatoprotective effects of Kappaphycus alvarezii (Doty) Doty ex Silva Against Carbon Tetrachloride-Induced Liver injury in Rats - Senty Vun-Sang; Gothai sivapragasam; Wilson Thau Lym Yong; Mohammad Amil Zulhilmi Benjamin; Mohammad Iqbal (Universiti Malaysia Sabah, 2024)
Kappaphycus alvarezii (Doty) Doty ex Silva, commonly known as red algae, holds economic significance as a primary source of κ-carrageenan, which exhibits promising medicinal and therapeutic properties. This study aims to assess the antioxidant potential as well as hepatoprotective activity of the ethanolic extract of K. alvarezii (EEKA). The assays utilised to determine the antioxidant properties of EEKA were total phenolic content (TPC) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging. In addition, the ability of EEKA to ameliorate experimentally induced liver injury in Sprague-Dawley rats caused by carbon tetrachloride (CCl4) was evaluated. The biochemical assays involved measuring liver marker enzymes (AST and ALT) in serum as well as determining the levels of reduced glutathione (GSH), lipid peroxidation (LPO) via malondialdehyde, catalase (CAT), and glutathione S-transferase (GST) in liver homogenates. The TPC and DPPH radical scavenging activity of EEKA demonstrated relatively low antioxidant properties compared to standard references. However, CCl4-induced groups exhibited significantly increased levels of AST and ALT, along with depletion of antioxidant status (GSH, CAT, and GST) indicated by LPO. Pretreatment with EEKA resulted in slightly decreased liver marker enzyme activity and LPO, coupled with an increase in antioxidant status. These findings suggest that EEKA contains active principles capable of counteracting the hepatotoxic effects induced by CCl4.